أثر مقرر إلكتروني معكوس على الأداء التدريسي ومهارات التفكير التأملي للطالبة المعلمة بكلية الاقتصاد المنزلي جامعة الأزهر - الشامي، إيناس عبدالمعز (كلية التربية جامعة 6 أكتوبر بالتعاون مع رابطة التربويين العرب, 2017)
هدف البحث: يهدف البحث إلى الوقوف على أثر استخدام مقرر إلكتروني معكوس على الأداء التدريسي ومهارات التفكير التأملي للطالبة المعلمة بكلية الاقتصاد المنزلي جامعة الأزهر. أهمية البحث: تنبع أهمية البحث مما يلي: مدى مساهمته في تنمية الأداء التدريسي للطالبة المعلمة بكلية الاقتصاد المنزلي جامعة الأزهر. مواكبته للاتجاهات التربوية الحديثة واستخدام التعلم النشط، والتعلم الذاتي، وتفريد التعليم، والاستفادة من المستحدثات التكنولوجية، في التعليم الجامعي. This study aims at investigating the effect of the use of a flipped electronic course on teaching performance and reflective thinking skills of the teacher female students at the Faculty of Home Economics, Al-Azhar University. The study sample consisted of 50 teacher female students in the fourth grade at the Faculty of home economics, Al-Azhar University in the scholastic year 2016/2017. They were divided into two groups after being randomly selected: a control group and an experimental group each consists of 25 students. To achieve the objectives of the study, the researcher used the descriptive analytic approach and the experimental approach. The tools and the material of the study were. the flipped electronic course in teaching methods (2), a teaching performance scale, and a reflective thinking test. The validity and reliability of both the three tools were assured through referees and applying them to a pilot group. After applying the study tools on the sample of the study and making the necessary statistical analyses by the SPSS processes such as T test and Eta, Correlation. The study drew several findings the most important of which are the following: There are statistically significant differences at the significance level (0.001≥α) between the mean scores of the control group and the experimental group in the teaching performance scale, and a reflective thinking test in favor of the experimental group.There are statistically significant differences at the significance level (0.001≥α) between the mean scores of the experimental group in the pre-and post testing of the teaching performance scale, and the reflective thinking test in favor of the post testing. The recommendations of the study: Encouraging the university education to use the flipped learning strategy and electronic courses in teaching students. It is necessary that university education should contain the Reflective Thinking skills in preparing the teacher students
Keywords: التعليم الجامعي -- إعداد المعلمين -- المقررات الإلكترونية -- الأداء التدريسي -- التفكير التأملي